The new SWOT for a sustainable world - Leandro Pereira; Miguel Pinto; Renato J. Lopes da Costa; Álvaro Lopes Dias; Rui Gonçalves (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
In today's complex and changing business environment the concern with sustainability has gained more notoriety. However, companies still do not have a sustainable perspective, but a short-term one, where their values are constantly forgotten and this concept is no longer welcomed. This research demonstrates the need for companies to adapt and to start acting in this direction. Following a set of interviews conducted with professionals with management positions of high responsibility, findings reveal that although sustainability is on the management mind, strategies and tools need to be adapted to be at the core of the organization's strategic formulation. To support this process, a new SWOT analysis to fit a forward-looking sustainable world is proposed. Furthermore, due to the aggregative nature of the model, it represents an essential tool for an open innovation. "SWOT i" integrates the concern with sustainability as one of its pillars, placing the values and impacts that each decision can have at the center of the strategic formulation, allowing their performance to leverage.
Keywords: 650; companies; performance; strategy; sustainability; SWOT i; tools; values